Study of Manure on Growth and Yield of White Glutinous Rice (Oryza Sativa L. Glutinosa) - nurjanah, siti; Nurhayati, Dewi Ratna; Siswadi, Siswadi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2020)
Research on